Competence of the bovine oocyte obtained by ovum pick-up as evaluated by the bright cresyl blue test - Ayala G., Luis (2018)
The objective of the present study was to evaluate the bright blue cresyl (BCB) test as an indirect method to select competent oocytes for the in vitro production of embryos (IVP). The cumulus-oocyte complexes (COC) were obtained from two Creole heifers subjected to two treatments: T1 = COC recovered by OPU (ovum pick-up) previous stimulation with FSH-LH; T2 = COC recovered from non-stimulated animals (control). The two heifers were alternated in the two treatments and five repetitions were done. Recovered COCs were classified into types A, B, C and D. Then the BCB test was applied to each of the COC types to determine if they were BCB+ or BCB-. T1 allowed to recover 5.2 more COC than T2 (p<0.05). When applying the BCB test, it was determined that all type A oocytes of T1 and T2 were BCB+; that is, they finished their growth and were ready to start the process of in vitro maturation; however, about 50% of the type B, C and D COCs of T1 and T2 were BCB+. It is concluded that the selection of COC based on morphological characteristics is a reliable method only for type A and has a 50% error for COC type B, C and D and, therefore, the application of the BCB test allows to improve this selection non-invasively.